Atypical Presentation of Traumatic Neuroma: A case report - Agrawal, Bela; Yadav, Ajit Kumar; Goel, Khushboo; Shrestha, Sajeev; Shrestha, Ashish (Journal of College of Medical Sciences-Nepal, 2017)
Congenital Traumatic neuroma is a rare disorder that represents a reactive proliferation of neural tissue followingdamage to an adjacent nerve. Rarely these lesions appear in the oral cavity with certain predilection for the mental foramen and the tongue area. However, its presentation on lip is more unusual with only few cases being reported in the literature. Typically diagnosed in middle-aged women, patient complains of pain as a frequent symptom. Clinically, the lip lesions appear as a normal or grayish white nodule with a smooth surface that typically resembles a mucocele. We report here a case of a 37-year old female who presented with similar signs and symptoms and was diagnosed clinically as a mucocele. However, histopathological examination revealed it as a traumatic neuroma that was surgically excised. The patient is under follow-up with no signs of recurrence for 18 months.